PELATIHAN DAN PENDAMPINGAN PENGGUNAAN APLIKASI MANAGEMENT STOCK CONTROL PADA UMKM PETERNAKAN LELE “RIZKY” KAMPUNG LELE BOYOLALI - Asih Handayani; Jemmy Bernardy; Dasmadi Dasmadi (LPPM Universitas Bina Bangsa, 2022)
The catfish village is a center for catfish farming in Boyolali Regency. Most of the people depend on the family economy from this sector. There are those who work as catfish breeders, consumption catfish breeders, feed sellers, catfish buyers, some are unskilled laborers in the farm. The IbM program is in collaboration with